If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(x+6)=7x+2
We move all terms to the left:
-(x+6)-(7x+2)=0
We get rid of parentheses
-x-7x-6-2=0
We add all the numbers together, and all the variables
-8x-8=0
We move all terms containing x to the left, all other terms to the right
-8x=8
x=8/-8
x=-1
| -8-2x=-x-6 | | 3x+(51-18)=180 | | 365-18d=185 | | 1/5x+13=x-7 | | -16/3=8y | | -2y-7=3. | | 5-2f=17 | | y=60+3(10) | | 2g-12=58 | | 3x+2=23, | | |2x-10|÷9=2 | | 108={x-3}x | | 5x-4=7(2x+2) | | 11x-2=84 | | y÷75=184 | | 16x-9+15x=189 | | 2x+2=3-x | | 48•u=6 | | |3x-10÷6|=7 | | -1y+15=-2(-6y+5) | | 3+2y-24=-3y | | -10+7/4p=-3 | | -4(x+13)=7(8x-10) | | 8(-5)+7y=-16 | | -24=3y-3 | | 3x-5=110 | | 22=7+21÷2x | | 23x+92=184 | | 7x–3=3x+25 | | -17=-2+5u | | 23x+96=184 | | 10x+8=4x+38 |